Estimating sequence diversity of prion protein gene (PRNP) in portuguese populations of two cervid species: Red Deer and Fallow Deer - Pereira, Jorge C. (2021)
Estimating sequence diversity of prion protein gene (PRNP) in portuguese populations of two cervid species: Red Deer and Fallow Deer